Relationship between exposure to Extremely Low‐Frequency (ELF) magnetic field and the level of some reproductive hormones among power plant workers - Suri, Sheari; Dehghan, Somayeh F.; Sahlabadi, Ali S.; Ardakani, Soheila K.; Moradi, Nariman; Rahmati, Maryam; Tehrani, Fahimeh R. (Journal of occupational health, 2020)
Background and Aims Today, human beings are exposed to the ELF magnetic field of electrical equipment and power lines, which can damage Leydig cells and alter the secretion of reproductive hormones. The purpose of this study was to investigate the relationship between exposure to ELF magnetic field and the level of some reproductive hormones in male power plant workers. Materials and Methods The present cross‐sectional study was carried out among all male employees of different units of the selected power plant around Tehran, Iran. All participants were asked to complete demographic data sheets and General Health questionnaire, on condition of consent and meeting the inclusion criteria. Time‐weighted average (TWA) exposure to magnetic field of 122 men was measured by IEEE Std C95.3.1 method using TES 1393 Gauss meter. Based on the exposure level, subjects were divided into three groups. Serum Levels of Free Testosterone, Luteinizing Hormone (LH), and Follicle stimulating hormone (FSH) in participants were determined. Data analysis was performed using ANOVA, Kruskal‐Wallis tests, and the relationships between variables were assessed by linear regression and correlation using SPSS v.25 software. Results There was no significant statistical correlation between the level of ELF exposure and serum levels of free testosterone, LH, and FSH, (r = 0.158). Serum levels of LH decreased significantly with age and duration of work experience (P < .05, r = −.25, P = .005, r = −.203, P = .025). Conclusion There was no relationship between exposure to magnetic field in power plants and reproductive hormone levels, although it is impossible to make definitive comments without using more accurate methods to estimate male fertility.